Pengaruh Penggunaan Metode Pembelajaran Resitasi Berbasis Model Pembelajaran Flipped-classroom Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Platform Komputasi Awan di SMK Negeri 6 Malang - Mohammad Daffa Saifullah; Admaja Dwi Herlambang; Tri Afirianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The good and efficient learning execution was the challenging for a teacher to do so actually to educating at vocational high school. It is because the student that were on vocational high school was be prepared to be able to work after graduating. And then to facilitate them to having a good learning outcomes and learning experience that they were expected to, so they need any education method or model that will be implemented on the class. This experiment will be more focused on use the resitation education method based on flipped-classroom education model within using Quasy-Experimental on Non-equivalent group kind. The execution of this experiment was to know the impact of using any education method or model on a experiment class compared to the other experiment class. When executing this experiment was found that learning outcomes that student received there is a difference that was showed with implementing t-test and there is an impact about using this education method and model that was showed by using N-Gain test, so the impact of experiment will be shown whether it is good or not to using the resitation education method based on flipped-classroom education model. From the calculation that has been done we can know that implementation of resitation education method based on flipped-classroom model has an impact compared by inquiry education method by 56.07% difference, so we can conclude that using this treatment can be categorized as Sufficiently Effective and can be implemented again by other teacher on the future class.